(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
This paper is based on the keynote address to the 14th International Association of Public and Non-Profit Marketing (IAPNM) conference. It explore the question "What impact do ethical values in the FairShares Model have on social entrepreneurial behaviour?" In the first part, three broad approaches to social enterprise are set out: co-operative and mutual enterprises (CMEs), social and responsible businesses (SRBs) and charitable trading activities (CTAs). The ethics that guide each approach are examined to provide a conceptual framework for examining FairShares as a case study. In the second part, findings are scrutinised in terms of the ethical values and principles that are activated when FairShares is applied to practice. The paper contributes to knowledge by giving an example of the way OpenSource technology (Loomio) has been used to translate ’espoused theories’ into ’theories in use’ to advance social enterprise development. The review of FairShares using the conceptual framework suggests there is a fourth approach based on multi-stakeholder co-operation to create ’associative democracy’ in the workplace.